PENGARUH MODEL PEMBELAJARAN PROBLEM BASED LEARNING (PBL) BERBANTUAN MEDIA PIRAMID PINTAR MATEMATIKA TERHADAP KEMAMPUAN PENALARAN MATEMATIS SISWA SD - Rizqita Shofia Nabila; Hesti Yunitiara Rizqi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the effect of the Problem Based Learning (PBL) model assisted by mathematical smart pyramid media on the mathematical reasoning abilities of elementary school students. The background of this research is the low mathematical reasoning ability of students who tend to only memorize formulas without understanding concepts. This research uses a quantitative method with a Quasi-Experimental design. The population in this study were all students of SDN [Nama Sekolah], with the sample divided into an experimental class using the PBL model and a control class using conventional models. Data collection techniques were carried out through pretest and posttest in the form of reasoning description questions. The results showed that there was a significant increase in the mathematical reasoning ability of students in the experimental class compared to the control class. This is evidenced by the results of the t-test and the average N-Gain value which shows that the use of the PBL model assisted by smart pyramid media is more effective in developing students' logical and systematic thinking patterns.